Saturday

April 19, 2014

April 19, 2014

Posted by **rohit** on Sunday, April 15, 2012 at 11:06am.

- math -
**Reiny**, Sunday, April 15, 2012 at 12:43pmsince x^2 - 3x + 2 = (x-2)(x-1)

so x^3 + ax^2 -bx + 10 must be divisible by both

x-2 and x-1

let f(x) = x^3 + ax^2- bx + 10

f(2) = 5 + 4a - 2b + 10 = 0 ---> 4a - 2b = -15

f(1) = 1 + a - b + 10 ---> a-b = -11 or a = b-11

sub 2nd into 1st

4(b-11) - 2b = -15

4b - 44 - 2b = -15

2b = 29

b = 29/2

then a = 29/2 - 11 = 7/2

**Related Questions**

algebra2 - solve the equation: First: x + 3y = 5 Second: 3x - y = 5 should i use...

maths - Write the system as a matrix equation and solve using inverses. x1 + 2x2...

Math - x2 + bx + c and ax2 + bx + c.

Math - x2 + bx + c and ax2 + bx + c.

ALG2 - x2 + bx + c and ax2 + bx + c could you factor this and explain it.

Math - Q.1)If one zero of the polynomial 3x2-kx-2 is 2 find the other zero.allso...

Math - Find the augmented matrix for each of the following systems of linear ...

Algebra - Quadratics (ZERO PRODUCT PROPERTY) - Can the Property of this: ax2 + ...

Calculus (Urgent!!) - Hello everyone, I need help with the following problems. ...

ALGEBRA - Could you explain how to factor the following trinomials : x2 + bx + c...